An Investigation into Salmonella Infection Status in Backyard Chickens in Iran - Jafari, R.A.; Ghorbanpour, M.; Jaideri, A. (International Journal of Poultry Science, 2007)
Salmonellosis is one of the most prevalent diseases in birds, causing high losses in poultry industry and food poisoning in human. For this reason, 422 apparently healthy chickens from 35 backyard flocks in different geographical regions of the rural area of Ahvaz (a city in the southwestern Iran) were sampled from January 2004 to June 2005 by cloacal swab as per OIE standards. The swabs, from each flock, were pooled in groups of up to five, then cultured and confirmed by routine biochemical and serological tests. Out of pooled 85 samples, five (5.8%) were positive for Salmonella. Of these, four isolates were identified as S. Serovar Typhimurium and one isolate as S. Serovar Enteritidis. The isolates belonged to 3 flocks. S. Serovar Enteritidis was sensitive in vitro to tetracycline, chloramphenicol, furazolidone, neomycine, nalidixic acid and sulfamethoxazole and trimethoprim, but the other four isolates were resistant to tetracycline and sulfamethoxazole and trimethoprim. This is the first report of the isolated serotypes in backyard chickens in Iran.